Tinjauan Hukum terhadap Aplikasi Digital sebagai Upaya Meningkatkan Kesadaran Perlindungan Hak Privasi Data Pribadi - Berto Purnomo Sidik; Sidi Ahyar Wiraguna (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
The protection of personal data privacy rights has become a crucial issue in the digital age. This research aims to analyze the effectiveness of digital applications in increasing public awareness regarding the importance of personal data protection and its legal implications. The research method employed is a literature study with a normative juridical approach, analyzing relevant laws and regulations on personal data protection, literature studies, and an analysis of the features of digital applications that focus on privacy education and control. The results of the study indicate that digital applications have significant potential in raising public awareness through the provision of easily accessible information, visualization of risks, and consent control mechanisms for data usage. However, their effectiveness heavily relies on intuitive interface design, clear and concise information delivery, and developers' compliance with personal data protection principles. This research recommends the need for more comprehensive regulations to ensure the quality standards and accountability of digital applications in educating the public about personal data privacy rights, as well as encouraging collaboration between developers, the government, and civil society organizations to create a safer and more privacy-aware digital ecosystem.